2015
DOI: 10.1002/jor.23130
|View full text |Cite
|
Sign up to set email alerts
|

Decreased elastic fibers and increased proteoglycans in the ligamentum flavum of patients with lumbar spinal canal stenosis

Abstract: Elastic fibers and proteoglycans are major components of the extracellular matrix and their changes have been reported in some pathological conditions. Further, recent studies have indicated that some glycosaminoglycans and proteoglycans inhibit elastic fiber assembly. The purpose of this study was to investigate changes of the elastic fibers and proteoglycans in the ligamentum flavum and analyze their relationships to thickening of the ligamentum flavum from lumbar spinal canal stenosis (LSCS). Ligamentum fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…The histology of many of these degenerative cyst contents has been described before and under various names. Changes seen in the histology of spinal stenosis include fibrosis, loss of elastic fibres, chondroid metaplasia, and deposition of calcium and proteoglycan matrix (similar to the myxoid material deposition described in the current cohort) . There are increased amounts of calcification in patients with lumbar spinal stenosis .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The histology of many of these degenerative cyst contents has been described before and under various names. Changes seen in the histology of spinal stenosis include fibrosis, loss of elastic fibres, chondroid metaplasia, and deposition of calcium and proteoglycan matrix (similar to the myxoid material deposition described in the current cohort) . There are increased amounts of calcification in patients with lumbar spinal stenosis .…”
Section: Discussionsupporting
confidence: 66%
“…Changes seen in the histology of spinal stenosis include fibrosis, loss of elastic fibres, chondroid metaplasia, and deposition of calcium and proteoglycan matrix (similar to the myxoid material deposition described in the current cohort). [4][5][6] There are increased amounts of calcification in patients with lumbar spinal stenosis. 7-10 Calcium pyrophosphate dihydrate crystal deposition (pseudogout) has been described in the LF, 11 sometimes as the cause of hypertrophy of the LF.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly composed of elastic fibers, collagen fibers, reticular fibers and matrix. Yabe demonstrated through Elastic-Mason staining and alcian blue staining that degenerative LF possess reduced elastic fibers and elevated proteoglycans levels compared to normal LF [5,18]. Our study found a significant increase in positive H&E and VVG stained elastic tissue from the dorsal aspect to the dural aspect in LSS group.…”
Section: Discussionsupporting
confidence: 52%
“…Fig. IIID) was known to suppress elastin assembly 21 and it was reduced in the fibroblast relative to PA SMC conditioned media at baseline and with BMP4 or TGFβ1 stimulation. We then reduced decorin in PA SMC by siRNA and showed production of dense elastic fibers, (Suppl.…”
Section: Resultsmentioning
confidence: 97%